Oxide thin films and nanostructures - Netzer, Falko P.; Noguera, Claudine (Oxford University Press, 2021)
Oxide Thin Films and Nanostructures is an interdisciplinary approach to introduce readers to the field of oxide nano-materials, that is oxides of nano-meter size and dimensions. Emphasis is put to differentiate these nanoscale oxide objects from their solid bulk oxide parents and present their properties in a pedagogic way.
Keywords: Thin films.; Oxides.; Nanostructured materials.; Nanostructures.; elektronické knihy; electronic books